PENGGUNAAN STRATEGI PEMBELAJARAN KONFLIK KOGNITIF DILENGKAPI HYPOTETHYCAL LEARNING TRAJECTORY PADA POKOK BAHASAN SUHU DAN KALOR DI SMA NEGERI 1 TANJUNG RAJA - Intan Megawati (Universitas Sriwijaya, 2014)
This study aims Â to determine the learning trajectory on the temperature and head material Research method was chosen is design research. This research was conducted at SMA Negeri 1 Tanjung Raja by involving 6 student in the pilot experiment phase and 35 student in teaching experiment phase. This example from learning trajectory on activity 1, the first conflict question